Knowledge and acceptance of COVID-19 vaccine among healthcare workers in Enugu metropolis, Enugu state, Nigeria - Imediegwu, Kelechi U.; Abor, Jude C.; Onyebuchukwu, Chiamaka Q.; Ugwu, Hilary I.; Ugwu, Ogechi I.; Anyaehie, Udo Ego; Onyia, Oluchi A. (Frontiers in Public Health, 2023)
BACKGROUND: COVID-19 disease spread at an alarming rate, and was declared a pandemic within five months from the first reported case. As vaccines have become available, there was a global effort to attain about 75% herd immunity through vaccination. There is a need to address the issue of vaccine hesitancy to COVID-19 vaccines especially in places such as Sub-Saharan African countries which have a high rate of background vaccine hesitancy. OBJECTIVE: To determine the knowledge and acceptance of COVID-19 vaccines among healthcare workers (HCWs) in Enugu metropolis. METHODS: A cross-sectional descriptive study of 103 HCWs in Enugu metropolis was done. Data was collected using structured online Google forms. Descriptive and inferential statistics was done using SPSS, and results were summarized into percentages and associations. RESULTS: An acceptance rate of 56.2% was obtained among HCWs in Enugu metropolis. Positive predicators of acceptance include older age (p = 0.004, X2 = 13.161), marriage (p = 0.001, X2 = 13.996), and higher average level of income (p = 0.013, X2 = 10.766) as significant correlations were found. No significant association was found between educational level, religion, denomination nor occupation and acceptance of vaccine. The major factor responsible for refusal was fear of side-effects. DISCUSSION: The acceptance rate of COVID-19 vaccines among HCWs is still less than optimal. This population represents the most enlightened population on health related matters, hence if acceptance rate remains merely average that in the general population is expected to be worse. There is a need to address the fear of vaccine side-effects by inculcating more open and interactive methods of information dissemination, while also addressing the misconceptions or myths surrounding COVID-19 vaccines.